Fatigue assessment by energy approach during tensile tests on AISI 304 steel - A. Risitano; D. Corallo; E. Guglielmino; G. Risitano; L. Scappaticci (Fracture and Structural Integrity)
Estimation of the fatigue limit for steel ductile materials using non-destructive methods is a topic of great interest to researchers today. In recent years, the method adopted has implemented infrared sensors to detect the surface temperature and correlate it with the fatigue limit. In previous paper, a new energy approach was proposed to investigate the fatigue limit during tensile test. The numerical procedure proposed by Chrysochoos is adopted to clean infrared images and applied to analyse the surface heat sources during tensile test. AISI 304 specimens with rectangular cross-sections are tested. Moreover fatigue tests at increasing loads were carried out on steel by a stepwise succession, applied to the same specimen, for applying the thermographic method. The predictions of the fatigue limit, obtained by the analysis of the energy evolution during the static tests, were compared with the predictions obtained applying the thermographic method during fatigue tests.